Diagnosis and treatmnet of poisoning and drug overdose - Devarajan, TV (New Delhi : Jaypee Brothers Medical Publishers, 2015)
This book Diagnosis and Treatment of Poisoning and Drug Overdose was long-awaited by medical students, postgraduate, general practitioners, casualty medical officers and ICCU doctors. This book has been prepared keeping in mind the necessity for guiding junior doctors and doctors in CCU to give first-aid, investigate and give proper antidote for drug overdose.
Contents 1.Poisoning: evaluation and treatment 2.Cholinergic agents poisoning 3.Actaminophen poisoning 4.Antiarrhythmic poisoning 5. Alchohols and glycols y otros
El texto esta en inglés
Incluye bibliografía e índice
Keywords: TRASTORNOS FETALES; DROGAS; ABUSO DE DROGAS